Dynamic Religious Acculturation: Exploring the Living Hadith Through the Ba'ayun Mawlid Tradition in Kalimantan - Agus Riwanda; Muh. Fathoni Hasyim (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
This paper presents a comprehensive examination of the ba’ayun mawlid tradition in South Kalimantan, offering a unique perspective on the living hadith and cultural acculturation within the context of Islam’s peaceful dissemination in the region. Originating as the Bapalas Bidan, a pre-Islamic ritual honoring supernatural spirits involved in childbirth, this tradition underwent a significant transformation after the advent of Islam, retaining its structure while embracing Islamic values and practices. Today, ba’ayun mawlid takes place in mosques under the guidance of religious leaders and midwives, featuring salawat in place of Kaharingan spells. This study delves into the diverse motivations driving community engagement in this tradition, including vow fulfillment, the annual zuriat ritual, the pursuit of blessings from sacred customs and locales, tawassul to nurture filial devotion and love for the Prophet, efforts to enhance livelihoods, cultural heritage preservation, and the evolution of ba’ayun mawlid into a form of religious tourism. Rooted in the prophetic hadith promising reunion with loved ones in the hereafter, this cultural phenomenon underscores the profound influence of religious practices on shaping values, identities, and the cultural landscape of the Banua Halat community. It provides valuable insights into the dynamics of acculturation and the enduring impact of religion on Indonesian society.